Comparison of Data Warehousing and Big Data Principles from an Economic and Technical Standpoint and Their Applicability to Natural Gas Remote Readout Systems - Kluk, Vedran; Dominika Crnjac Milić; Krpić, Zdravko (International Journal of Electrical and Computer Engineering Systems, 2019)
In the remote reading of natural gas a large amount of data is collected, facing the companies involved with the problem of storing and processing such data. More recently two major technologies appeared, de-facto becoming a standard in processing large amounts of data: Data Warehousing and Big Data. Each of these technologies provides different data processing techniques; In this paper serial data processing is considered in Data Warehousing while and parallel data processing in Big Data. The paper analyzes the feasibility of implementing new technologies for processing large amount of data generated by the remote reading of natural gas consumption. The research conducted in this paper was made in collaboration with the local natural gas distributer. The comparison of potential software vendors has shown that Qlik offers the best software package for the requirements provided by the local natural gas distributor. The comparison results have also shown that the other potential vendors also offer quality software packages.